BUSINESS FEASIBILITY ANALYSIS IN THE ESTABLISHMENT OFA CAFE - Kurniawan, Ridho Raditya; Taufik, Irham; Putri, Mawar; Safira, Mia; Fransiska, Dara Anggun (Proceeding International Seminar of Islamic Studies, 2023)
As a basic human need, culinary is seen developing widely over the years in Indonesian society. This culinary industry has been proven by contributing large numbers in the national economy. Based on data, national tourism and creative economy have provided around 30% of the total national economic income. In this case, the government provides a statement to support all culinary sub -sectors in Indonesia. One of the creative industries that is developing rapidly in Indonesia is food and beverages or culinary industries. At present the food and beverage industry is a sector with the largest contribution of Indonesia's economy, which is 5.5 percent of the national gross domestic product and 31 percent of gross domestic product in non-miny and industrial gas processing. This makes Indonesia high potential in the culinary field. Seeing the fast development of the culinary world in Indonesia, more and more restaurants, cafes, or eating where Indonesia appears. Feasibility study is a tool that can be taken into consideration in making The decision to accept or reject the proposed investment in developing or establishing project/business planning. Research on business feasibility analysis, not to know whether it is feasible or not from the value of investment criteria.